Use QR Code and IoT Mobile Devices to Prevent the Spread of an Epidemic (COVID-19) - Radhi, Ahmed A. (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The spread of new pandemic novel Corona-Virus (COVID-19) brought violent changes in livelihood. It was difficult to control and cause Curfew in many countries, disrupted life, Imposing conditions for social distancing, masks because of unavailable of drugs, and treatments. The aim of this paper is using QR code and IoT for prevention transmission of COVID-19 by making electronic medical register for each human stored in cloud database included periodic Corona-Virus test and generate unique QR code for each one on the other side two software applications designed one for monitoring and update information of the medical register in the cloud and the second software read QR code and control the gates of public locations via IoT, as the results only healthy people can travel among public locations (markets, malls, Universities, Subways,…etc) and the infected persons can be monitored.